2014
DOI: 10.1093/mnras/stu2226
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the magnetorotational instability to the shear parameter in stratified simulations

Abstract: The magnetorotational instability (MRI) is a shear instability and thus its sensitivity to the shear parameter q = −d ln Ω/d ln r is of interest to investigate. Motivated by astrophysical disks, most (but not all) previous MRI studies have focused on the Keplerian value of q = 1.5. Using simulation with 8 vertical density scale heights, we contribute to the subset of studies addressing the the effect of varying q in stratified numerical simulations. We discuss why shearing boxes cannot easily be used to study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 29 publications
7
27
1
Order By: Relevance
“…There have been specific attempts to improve the closure (Ogilvie 2003;Pessah, Chan & Psaltis 2006), and more recent direct evidence that the MRI stress does not agree with the SS73 formulation (Pessah, Chan & Psaltis 2008;Nauman & Blackman 2015). As discussed further below, our interpretation of numerical evidence further suggests that the transport from the MRI is actually dominated by large scales.…”
Section: Standard Disc Theory Does Not Distinguish Local Versus Non-lmentioning
confidence: 82%
See 2 more Smart Citations
“…There have been specific attempts to improve the closure (Ogilvie 2003;Pessah, Chan & Psaltis 2006), and more recent direct evidence that the MRI stress does not agree with the SS73 formulation (Pessah, Chan & Psaltis 2008;Nauman & Blackman 2015). As discussed further below, our interpretation of numerical evidence further suggests that the transport from the MRI is actually dominated by large scales.…”
Section: Standard Disc Theory Does Not Distinguish Local Versus Non-lmentioning
confidence: 82%
“…Using the above procedure for a q = 3/2 case from a run with 32 zones/H and domain size H × 2H × 4H (Nauman & Blackman 2015), we find that the ratio of the stresses from the mean field to that of the total to be T M,xy /T xy 0.24 and the ratio of magnetic energy from the mean field to that of the total to be 0.47. These indicate a significant contribution from the mean field, bolstering the overall message that large-scale fields and transport are important.…”
Section: Comparing Stresses From Mean Fields To Those From Fluctuationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Nauman & Blackman (2015) and Gressel & Pessah (2015) found that the dynamo period becomes shorter and less well-defined (e. g. see the butterfly diagram for q = 1.8 in Fig. 6 in Nauman & Blackman (2015)) when the shear parameter q is increased from its Keplerian value. Interestingly, in the quasi-steady state of our simulations the angular velocity is sub-Keplerian with Ω = v φ r ∝ r −1.7 (see equation 42).…”
Section: Dynamomentioning
confidence: 99%
“…Hawley, Gammie & Balbus 1995;Sorathia et al 2012;Hawley et al 2013) confirmed that MRI can sustain turbulence and dynamo in accretion discs. However, semi-analytical and numerical simulations (see, for example, Masada & Sano 2008;Stone 2011;Hawley et al 2013;Suzuki & Inutsuka 2014;Nauman & Blackman 2015) suggest that the total (Reynolds + Maxwell) stresses due to MRI are insufficient to cause the effective angular momentum transfer in accretion discs in terms of the phenomenological alpha-parameter α S S (Shakura & Sunyaev 1973), giving rather low values α S S ∼ 0.01 − 0.03. Note that from the observational point of view, the alpha-parameter can be reliably evaluated, e.g., from the analysis of non-stationary accretion discs in X-ray novae (Suleimanov, Lipunova & Shakura 2008), dwarf-nova and AM CVn stars (Kotko & Lasota 2012), and turns out to be an order of magnitude higher than typically found in the numerical MRI simulations.…”
Section: Introductionmentioning
confidence: 99%